KAJIAN TINGKAT KENYAMANAN FISIK RUANG DALAM UNIT HUNIAN RUMAH SUSUN DAAN MOGOT JAKARTA BARAT - Ulinata, Ulinata (Jurnal Koridor, 2021)
Planning and Construction of Daan Mogot Flats, West Jakarta using green building concept is the Government's effort to solve problem of housing needs for residents who do not have housing and low income. The planning and construction of Daan Mogot Flats, West Jakarta is a pilot project by the DKI Jakarta Provincial Government which is expected to create healthy, comfortable and effective housing for its residents and become example for other flats. The research entitled Study of Physical Comfort Level Space in the Residential Unit of Daan Mogot Flats, West Jakarta, have a purpose to know the extent of the comfort of the space in flat's residential unit when inhabited. This research is using quantitative method by instrument in the form of 40 respondents. The results show that level of physical comfort space in the residential unit of Daan Mogot Flats, West Jakarta is quite good, but there is still something needs to be improved, including the adequacy and quality of space that should be occupied by one family so that the adequacy and quality of space is more adequate, more optimize natural ventilation, use public facilities as selling areas not in residential units in order to obtain space suitability.